PENERAPAN METODE GUIDED NOTE TAKING DALAM PEMBELAJARAN - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The learning method is a method or procedure used to facilitate the implementation of the learning process in the learning environment. One method that can be applied in the learning process is the Guided Note Taking method. Guided Note Taking is a guided note taking method in which the teacher provides a prepared form or sheet, this width instructs students to take notes while teaching. The purpose of this method is so that the lecture method that the teacher gives can develop and get students' attention and can turn boring material into fun material. This method will also make students more focused and active in participating in learning. The learning process with this method will direct the concentration of students in taking important points from teaching materials in the form of handouts that students listen to. The Guided Note Taking method emphasizes students to listen, remember and then write the material explained by the teacher during the learning process.